2021
DOI: 10.1186/s13643-021-01670-0
|View full text |Cite
|
Sign up to set email alerts
|

The REPRISE project: protocol for an evaluation of REProducibility and Replicability In Syntheses of Evidence

Abstract: Background Investigations of transparency, reproducibility and replicability in science have been directed largely at individual studies. It is just as critical to explore these issues in syntheses of studies, such as systematic reviews, given their influence on decision-making and future research. We aim to explore various aspects relating to the transparency, reproducibility and replicability of several components of systematic reviews with meta-analysis of the effects of health, social, beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…Some studies have explored these barriers in general academia (40,41), but we are uncertain whether researchers in evidence synthesis will face all of these barriers or even unidentified barriers unique to systematic reviews and meta-analyses. Future studies in the REPRISE project will explore systematic reviewers’ perspectives on barriers and incentives to reporting and data-sharing in order to address these questions (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have explored these barriers in general academia (40,41), but we are uncertain whether researchers in evidence synthesis will face all of these barriers or even unidentified barriers unique to systematic reviews and meta-analyses. Future studies in the REPRISE project will explore systematic reviewers’ perspectives on barriers and incentives to reporting and data-sharing in order to address these questions (25).…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted as one of a suite of studies in the REPRISE (REProducibility and Replicability In Syntheses of Evidence) project. The REPRISE project is investigating various aspects relating to the transparency, reproducibility and replicability of systematic reviews with meta-analysis of the effects of health, social, behavioural and educational interventions (25). Methods for all studies were pre-specified in the same protocol (25).…”
Section: Methodsmentioning
confidence: 99%
“…28 The study's findings are reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. 29…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for opting for a narrative review in this study is to outline what has been previously published on the topic and seek new study areas not yet explored [50,51]. Nonetheless, each step of the review was informed by the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) reporting guidelines [52,53].…”
Section: Review Scope and Methodsmentioning
confidence: 99%
“…Additional gray literature and scholarly materials, including working papers, dissertations, and book sections, were manually searched using institutional websites, Google Scholar, and snowballing through review of references in the identified publications. Full information on MeSH terms, keywords, and Boolean operators used and search strategy developed for each database is provided in the Supplementary Materials (Table S1) to improve reproducibility of results [52]. All publications that reported results from an original quantitative or qualitative research study on the impact of voluntary IP models on indicators of access to medicines were included.…”
Section: Review Scope and Methodsmentioning
confidence: 99%